KOMPYUTERLI MODELLESTIRIW TEXNOLOGIYASÍN PAYDALANÍW BOYÍNSHA METODIKALÍQ PIKIRLER - Eshanov, M.; Sarsenbaev, D.; Muxiyatdinova, A. (ILIM hám JÁMIYET, 2023)
This article is analyzed the relevance of computer modeling technologies and scientific methodological concepts used in the modeling system.